The impact of globalization on the performance of banks in South Africa - Sufian, Fadzlan; Kamarudin, Fakarudin (Emerald Publishing, 2016)
Purpose – This paper aims to provide empirical evidence for the impact globalization has had on the performance of the banking sector in South Africa. In addition, this study also investigates bank-specific characteristics and macroeconomic conditions that may influence the performance of the banking sector. Design/methodology/approach – The authors use data collected for all commercial banks in South Africa between 1998 and 2012. The ratio of return on assets was used to measure bank performance. They then used the dynamic panel regression with the generalized method of moments as an estimation method to investigate the potential determinants and the impact of globalization on bank performance. Findings – Positive impact of greater economic integration and trade movements of the host country, while greater social globalization in the host country tends to exert negative influence on bank profitability. The results show that banks originating from the relatively more economically globalized countries tend to perform better, while banks headquartered in countries with greater social and political globalizations tend to exhibit lower profitability levels. Originality/value – An empirical model was developed that allows for the performance of multinational banks to depend on internal and external factors. Moreover, unlike the previous studies on bank performance, in this empirical analysis, we control for the different dimensions of globalizations while taking into account the origins of the multinational banks. The procedure allows us to test for the home field, the liability of foreignness and global advantage hypotheses to deduce further insights into the prospects of banking across borders.